Temperatura do solo como uma resposta ao estímulo da radiação solar - Rodrigues Oliveira, Francisco; C Sediyama, Gilberto; Vieira, Manoel; Teixeira Coelho, Dirceu (Revista Ceres, 2025)
Using daily TS data observed in Viçosa, MG, from 1971 thru 1976, a Fourier series was adjusted to approach the function h. From the results of the integration of the convolution expression, TS(t), the simulated soil temperature data were compared to observed TS data for 1977 using daily global RS data for 1, 6 and 12 previous days.